Does whey protein supplementation during resistance exercise have additional benefits for decreasing hepatic fat content? - Chae-Been Kim; Hyoung-Su Park; Hye-Jin Kim; Hong-Soo Kim; Jung-Jun Park (Taylor & Francis Group, 2023)
Background Exercise and diet have positive effects on hepatic fat reduction, and protein supplementation is known to lower hepatic fat accumulation. However, the effect of a combination of exercise and whey protein supplementation (WPS) on hepatic fat content (HFC) is unknown. Methods We investigated the effect of WPS on HFC during resistance exercise and diet control intervention for four weeks. A total of 34 sedentary males participated and were randomly assigned to two groups: a protein supplement group (PSG, n = 18) and a control group (CG, n = 16). The PSG took 60 g of WPS per day, and the CG took 60 g of an isocaloric placebo per day. All participants were fed a calorie-controlled diet throughout the study period, with their daily caloric intake determined by their resting metabolic rate and physical activity level. Both groups performed resistance exercises supervised by experts at 60-70% of their maximum efforts for 60 min/day, 6 days/week for 4 weeks. HFC was assessed using the controlled attenuation parameter (CAP) after an 8 h fast, at pre-, mid-, and post-intervention. Liver enzymes and lipid profile were also analyzed after an 8 h fast and pre- and post-intervention. Results The CAP was significantly reduced after 4 weeks of intervention in both groups (PSG, p < .001; CG, p = .002). However, there was no significant interaction between the group and changes in CAP. Interestingly, when comparing the pre- and mid-tests, both groups also had significantly reduced CAP (PSG, p = .027; CG, p = .028), but there was a significant difference in the amount of change in CAP between the two groups (PSG, -47.2 ± 25.4 dB/m; CG, -19.5 ± 15.1 dB/m; p = .042). For liver enzymes, there was a significant interaction between the two groups and a change in aspartate transaminase (AST) (p = .038). However, alanine aminotransferase (ALT) levels were significantly decreased only in the PSG group (p = .002). In lipids, both groups showed significantly decreased total cholesterol (p < .001) and low-density lipoprotein cholesterol (p < .001) after the intervention. Conclusion Our data showed that WPS may not enhance the overall effects of resistance exercise on HFC and lipid profiles. However, in part, WPS may have a beneficial effect on liver enzymatic changes and rapid response to resistance exercise-induced HFC reduction.